Cognition and psychotherapy - Freeman, Arthur, 1942- (Springer Pub., 2004)
In the first edition, recognized specialists from the major ideological schools address the role and conceptualization of cognitive processes and procedures of the psychotherapeutic encounter. In the almost two decades since the publication of the first edition, the "cognitive revolution" has moved from being a barbarian by the gate of the establishment to having become the establishment. This revised work reflects the convergent themes noted across approaches to psychotherapy. Several of the earlier contributions have been updated and offer more contemporary views. Finally, the edit.